Analisis Pengaruh Dana Bos, Program Indonesia Pintar, Bansos, dan Pertumbuhan Ekonomi Terhadap IPM di Jawa Tengah (2019-2023) - Putri, Vienda Aprilia; Arif, Muhammad (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of School Operational Assistance Funds, Smart Indonesia Program, Social Assistance, and Economic Growth on the Human Development Index (HDI) in Central Java Province for the period 2019-2023. This study uses quantitative analysis methods and uses panel data regression analysis with the selected model being the Fixed Effect Model (FEM). The results of this study indicate that School Operational Assistance Funds and Social Assistance have a negative and significant effect on the Human Development Index (HDI), and Economic Growth has a positive and significant effect on the Human Development Index (HDI). Meanwhile, the Smart Indonesia Program does not have a significant effect on the Human Development Index (HDI) in Central Java Province for the period 2019-2023.